Effect of botulinum toxin on improving quality of life in patients with chronic migraine - Marzęda, Magdalena; Swatko, Tomasz; Blicharz, Agnieszka; Stachura, Tomasz; Kamieniak, Maciej; Jarosz, Piotr; Kobiałka, Izabela (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Migraine is a chronic condition affecting up to 10% of the adult population in Poland. Migraine pain is severe and may be accompanied by nausea or vomiting, as well as hypersensitivity to light, sounds or smells. Chronic form of migraine means the occurrence of headache a minimum of 15 days per month, for a period of at least three months, of which eight days or more of pain meet the criteria for migraine pain. The chronic form of migraine is targeted for treatment with botulinum toxin, a neurotoxin secreted by the bacteria Clostridium botulinum. Brief description of the state of knowledge: The pathogenesis of migraine is still unknown. There are many hypotheses explaining the origin of migraine pain, of which the most plausible seems to be the theory involving the trigeminal nerve system, as well as trigger points in the head and neck area. Their activation leads to the triggering of pain. Botulinum toxin has been used to treat migraine for several years. The only registered drug is Botox, the effectiveness of which has been confirmed in clinical studies. The preparation is administered by injection into the muscles of the head and neck region in cycles with an interval of 12 weeks. Botulinum toxin works by blocking the release of inflammatory and pain mediators from the trigeminal nerve endings. Summary: Chronic migraine refers to the occurrence of headache for more than half of the month, which significantly reduces the quality of life of people worldwide. Migraine headaches often refractory to pharmacological treatment may respond well to botulinum toxin type A. Therapy should be under the supervision of a neurologist, who will familiarise the patient with the expected effects of botulinum toxin treatment before starting treatment.